Evaluations of Ovarian and Luteal Blood Flow Waveform Patterns in Buffalos Subjected to OvSynch Protocol in Cold and Hot Seasons - Sayed, Mohamed Fathy; Abdelnaby, Elshymaa A.; El-Shahat, Khaled; Abd-Allah, Saber (Journal of Buffalo Science, 2022)
This current study aimed to determine ovarian and luteal blood flow waveform patterns in buffalos synchronized using OvSynch protocol in cold and hot seasons. Six cyclic buffalo cows aged 6±0.5 years old, having a weight of 400 ± 50 kg, were scanned daily along three successive estrous cycles transrectally by Doppler ultrasonography to evaluate the normal ovarian hemodynamic during the normal spontaneous ovulation and before the start of experiments. Buffaloes were synchronized with gonadotropin[GnRH] –prostaglandin[P] –gonadotropin (GPG) protocol in which animals received 10μg of GnRH on day ??, 0.250μg of PGF2α on day 7, and another dose of 10μg of GnRH was administered 48h after the PGF2α injection. Blood sampling and ovarian ultrasound examinations (color and spectral Doppler modes) were conducted on the day of the estrous and luteal phases. Results revealed that peak systolic velocity waveform (PSV) was significantly (P<0.05) increased in the cold season compared to the hot season. The Luteal blood flow after the end of OvSynch protocol on days (5,7,9, and 11) was significantly increased in the cold season than that in the hot one. The serum levels of estradiol (E2) and nitric oxide (NO) after the second GnRH injection in the OvSynch protocol were significantly (P<0.05) elevated in the cold season as compared to the hot one. Moreover, the progesterone (P4) levels had risen in OvSynch-treated buffaloes on days 5,7,9, and 11 of the cycle in the cold season compared to the hot one. Conclusion: In the cold season, ovarian hemodynamics was significantly improved compared to the hot one; this may influence the reproductive efficiency of buffaloes. Further studies were needed to prove it.